IMPLEMENTATION OF THE PEKANBARU MAYOR’S REGULATION OF PEKANBARU NUMBER 16 YEAR 2017 CONCERING THE PLENARY MOSQUE AL - UKHWAH GROUP MANAGEMENT AIR PUTIH VILLAGE DISTRICT TAMPAN IN 2017 - Desmafitri "; Wan Asrida (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
In achieving the vision of Pekanbaru City in 2012-2017 "Realizing Pekanbaru as a Metropolitan City that is Madani", the Pekanbaru city government brought up the idea of a Plenary Mosque. To support this vision, the Pekanbaru city government set the Pekanbaru Mayor Regulation Number 16 of 2017 concerning Guidelines for the Management of the Pekanbaru City Plenary Mosque. To see the Pekanbaru City government policy regarding the Pekanbaru Mayor Regulation, the researchers want to see the Implementation of the Pekanbaru Mayor Regulation Number 16 of 2017 concerning Guidelines for Al-Ukhwah Plenary Mosque Management in Air Putih Village, Tampan District In 2017,This study aims to (1) to describe the Implementation of Pekanbaru Mayor Regulation Number 16 of 2017 Regarding the Al-Ukhwah Plenary Mosque Management Group in Air Putih Village, Tampan District In 2017 (2) to find out the inhibiting factors Implementation of Pekanbaru Mayor Regulation Number 16 of 2017 Regarding the Al-Ukhwah Plenary Mosque Management Agency in Air Putih Village, Tampan District In 2017. The location of the research was conducted at the Al-Ukhwah Plenary Mosque Air Putih Village. Data collection techniques are carried out by interviews and documentation. While the data analysis technique is done by qualitative data analysis.The results of the study the Implementation of Pekanbaru Mayor Regulation Number 16 of 2017 Regarding the Al-Ukhwah Plenary Mosque Management Group in Air Putih Village, Tampan District In 2017 has not run optimally at Al-Ukhwah Plenary Mosque Air Putih Village seen from the management of the Plenary Mosque program that has been carried out namely in the field of Idarah (Mosque management) is still not optimal and complete, Imarah(Prosperity of the mosque) the number of worshipers is still small, activities have not been well realized, Ri'ayah (mosque facility maintenance) there are still many damaged mosque facilities. The inhibiting factor is the lack of communication between the responsible party and the management body itself, limited budget funds only for operational salaries, lack of infrastructure facilities there are still many mosque facilities that are damaged and lack of supervision carried out by the City government and the District as supervisors of the Plenary Mosque of the Village.Kata Kunci : Implementation, Policy, Management